Analisis Putusan Ma Nomor: 261 K/Pdt.Sus/2011 Mengenai Sengketa Merek Dagang Antara Paimin Halim Dan Abdul Alex Soelystio - Wishnu Kurniawan; Erni Yuliani (Fakultas Hukum, Universitas Internasional Batam, 2014)
The world economy continues to grow to adulthood, because the goods or services produced by the company is required distinctive mark, the purpose of difference is to give a name, marks, symbols or colors that are often known by the brand. The research problem is how the provision the use of brands in terms of the Act and the Trademark Is Supreme Court ruling Number 261 K / PDT.SUS / 2011 in accordance with Law number of 15 of 2001 on Marks.This research uses normative research which describe the legislation that apply, especially in Act 15 of 2001 on Trademark linked with legal theories in practice related to implementation of the problems studied by the author. Secondary data collected for study was conduted through library research to the material that the relevant law.Based on this study towards the cases can be concluded that the Trademark violation committed by Abdul Alex Soelystio that is using its trademark called